Endoscopic Interhemispheric Disconnection for Intractable Multifocal Epilepsy: Surgical Technique and Functional Neuroanatomy. Issue 2 (29th May 2019) - Sufianov, Albert A; Cossu, Giulia; Iakimov, Iurii A; Sufianov, Rinat A; Markin, Egor S; Stefanov, Stefan Z; Zemmoura, Ilyess; Messerer, Mahmoud; Daniel, Roy T
Abstract: BACKGROUND: Callosotomy represents a palliative procedure for intractable multifocal epilepsy. The extent of callosotomy and the benefits of adding anterior and posterior commissurotomy are debated. OBJECTIVE: To describe a new technique of a purely endoscopic procedure to disconnect the corpus callosum, the anterior, posterior, and habenular commissures through the use of a single burr hole via a transfrontal transventricular route. METHODS: Our surgical series was retrospectively reviewed in terms of seizure control (Engel's class) and complication rate. Five cadaveric specimens were used to demonstrate the surgical anatomy of commissural fibers and third ventricle. RESULTS: The procedure may be divided into 3 steps: (1) endoscopic transventricular transforaminal anterior commissure disconnection; (2) disconnection of posterior and habenular commissures; and (3) total callosotomy. Fifty-seven patients were included in the analysis. A favorable outcome in terms of epilepsy control (Engel class 1 to 3) was found in 71.4% of patients undergoing callosotomy coupled with anterior, posterior, and habenular commissure disconnection against 53% of patients with isolated callosotomy ( P = .26). Patients with drop attacks had better epilepsy outcome independently from the surgical procedure used. CONCLUSION: The full endoscopic callosotomy coupled with disconnection of anterior, posterior and habenular commissures is a safe alternative to treat multifocal refractory epilepsy. A gain in seizure outcome might be present in this cohort of patients treated with total interhemispheric disconnection when compared with isolated callosotomy. Larger studies are required to confirm these findings.